2022
DOI: 10.1039/d2cp01507b
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4/TiO2-B{100} heterostructures used as promising photocatalysts for water splitting from a hybrid density functional study

Abstract: Fabrication of heterostructure has been shown to be a good strategy to improve photocatalytic performance. By using first-principles calculation based on hybrid density functionals, photocatalytic mechanism of g-C3N4/TiO2-B{100} heterostructures is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…It is found that the geometry of F N2 @g-C 3 N 4 is a distorted open-ring structure due to the overwhelmingly strong Coulomb repulsion between the lone pair electrons on pyridine nitrogen atoms and the high electronegativity of the F atom. Compared with the band structures of pure g-C 3 N 4 in our previous study, 17 F doping promotes the overall band structures of g-C 3 N 4 to move toward the lower energy, indicating that the F-substitutiondoped g-C 3 N 4 is more stable. It is worth noting that F doping creates few impurity levels inside the band gap, which are attributed to C1 and C2 atoms nearby the dopant F atom, as one can see in Figure 1c,d.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that the geometry of F N2 @g-C 3 N 4 is a distorted open-ring structure due to the overwhelmingly strong Coulomb repulsion between the lone pair electrons on pyridine nitrogen atoms and the high electronegativity of the F atom. Compared with the band structures of pure g-C 3 N 4 in our previous study, 17 F doping promotes the overall band structures of g-C 3 N 4 to move toward the lower energy, indicating that the F-substitutiondoped g-C 3 N 4 is more stable. It is worth noting that F doping creates few impurity levels inside the band gap, which are attributed to C1 and C2 atoms nearby the dopant F atom, as one can see in Figure 1c,d.…”
Section: Resultsmentioning
confidence: 99%
“…The narrower band gap leads to the high utilization efficiency of visible light, and the suitable band alignment can effectively separate photoinduced electrons and holes. Our previous study 17 found that compared with the band gap of the TiO 2 -B bulk (3.22 eV), 18 the band From the projected weighted band structures and density of states for the F N2 @g-C 3 N 4 /TiO 2 -B(001) heterostructure as shown in Figure 4a,b, we can see that the band structures of F N2 @g-C 3 N 4 are weakly influenced by the substrate TiO 2 -B(001) surface. We note that the profile of the band structures of F N2 @g-C 3 N 4 in the heterostructure as well as its freestanding form are similar due to the weak interaction between layers in the F N2 @g-C 3 N 4 /TiO 2 -B(001) heterostructure, except for the energy shift and local perturbation, which one can see from Figures 1d and 4a.…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations